Bamboo: Potential for bioenergy and landscape restoration in Indonesia - Sharma, R.; Wahono, J.; Andini, S.; Baral, H. (Center for International Forestry Research, 2022)
The growing demand for energy in Indonesia is driven by population growth, urbanization and economic development. Meeting this energy demand while reducing dependence on fossil fuels is vital. As Indonesia has a rich biomass base, bioenergy has become an important component of the nation’s energy agenda. However, a crucial problem with bioenergy production is its potential impacts on food security, the environment and biodiversity. In this context, we discuss the characteristics, benefits and challenges of using bamboo, a perennial grass, as a potential provider of bioenergy feedstock in Indonesia. We describe the fuel characteristics of bamboo and the possibility of aligning its cultivation, production and utilization with environmental and development agendas. Its rapid growth, long root systems, easy maintenance and ability to grow in harsh conditions indicate its potential for use in restoring degraded lands. Therefore, we recommend in-depth research on the social, ecological and economic feasibility of using bamboo for bioenergy production.